Antibiotic and Metal Resistance in Escherichia coli Isolated from Pig Slaughterhouses in the United Kingdom - Hongyan Yang; Shao-Hung Wei; Jon L. Hobman; Christine E. R. Dodd (MDPI AG, 2020)
Antimicrobial resistance is currently an important concern, but there are few data on the co-presence of metal and antibiotic resistance in potentially pathogenic Escherichia coli entering the food chain from pork, which may threaten human health. We have examined the phenotypic and genotypic resistances to 18 antibiotics and 3 metals (mercury, silver, and copper) of E. coli from pig slaughterhouses in the United Kingdom. The results showed resistances to oxytetracycline, streptomycin, sulphonamide, ampicillin, chloramphenicol, trimethoprim-sulfamethoxazole, ceftiofur, amoxicillin-clavulanic acid, aztreonam, and nitrofurantoin. The top three resistances were oxytetracycline (64%), streptomycin (28%), and sulphonamide (16%). Two strains were resistant to six kinds of antibiotics. Three carried the blaTEM gene. Fifteen strains (18.75%) were resistant to 25 µg/mL mercury and five (6.25%) of these to 50 µg/mL; merA and merC genes were detected in 14 strains. Thirty-five strains (43.75%) showed resistance to silver, with 19 possessing silA, silB, and silE genes. Fifty-five strains (68.75%) were resistant to 8 mM copper or above. Seven contained the pcoE gene. Some strains were multi-resistant to antibiotics, silver, and copper. The results in this study, based on strains isolated between 2007 and 2010, will aid understanding about the effects of strategies to reduce resistance and mechanisms of antimicrobial resistance (AMR).